Design of respirable sprayed microparticles of encapsulated bacteriophages - Baldelli, Alberto; Liang, Mingtao (Frontiers in Drug Delivery, 2023)
Antibiotic resistance is exponentially increasing, and the number of deaths caused by bacterial infections is expected to surge. When dealing with the respiratory system, inefficient antibiotics heighten the chance of death from bacterial infection. However, the alternatives to antibiotics are limited. Bacteriophages are a valid option since they can target a specific type of bacterium. Bacteriophages are highly specific and can avoid any side effects when delivered. However, their poor stability makes their use inefficient. Encapsulation is commonly used to protect any bioactive compound for different types of delivery. In the case of respiratory delivery, particle engineering is used to generate stable dry powders to target the nasal or lung areas. This review article provides a guideline for engineering a process of nasal dry powders of encapsulated bacteriophages.